2012
DOI: 10.1152/japplphysiol.00884.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments of pulmonary O2 uptake and muscle deoxygenation during ramp incremental exercise and constant-load moderate-intensity exercise in young and older adults

Abstract: The matching of muscle O(2) delivery to O(2) utilization can be inferred from the adjustments in muscle deoxygenation (Δ[HHb]) and pulmonary O(2) uptake (Vo(2p)). This study examined the adjustments of Vo(2p) and Δ[HHb] during ramp incremental (RI) and constant-load (CL) exercise in adult males. Ten young adults (YA; age: 25 ± 5 yr) and nine older adults (OA; age: 70 ± 3 yr) completed two RI tests and six CL step transitions to a work rate (WR) corresponding to 1) 80% of the estimated lactate threshold (same r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 63 publications
4
23
0
1
Order By: Relevance
“…This suggests that the slower dynamic adjustment of oxidative phosphorylation typically observed in older individuals might be secondary to other factors such as training status, instead of being exclusively determined by aging per se. Indeed, in three other studies in which V O 2 kinetics responses were compared in older and young individuals, the rate of adjustment of oxidative phosphorylation was similar between groups (12,13,38). In addition, a recent paper has demonstrated that older, chronically trained men have V O 2 kinetics that is similar to those of young individuals (39).…”
Section: O 2 Kinetics In Older Adultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This suggests that the slower dynamic adjustment of oxidative phosphorylation typically observed in older individuals might be secondary to other factors such as training status, instead of being exclusively determined by aging per se. Indeed, in three other studies in which V O 2 kinetics responses were compared in older and young individuals, the rate of adjustment of oxidative phosphorylation was similar between groups (12,13,38). In addition, a recent paper has demonstrated that older, chronically trained men have V O 2 kinetics that is similar to those of young individuals (39).…”
Section: O 2 Kinetics In Older Adultsmentioning
confidence: 89%
“…Babcock and colleagues originally noted little change in the HR dynamics across age (30-80 yr) (3) and that with training the faster HR kinetics were not related to the faster V O 2 kinetics (2). Nevertheless, other studies have found that THR was significantly greater in older compared with young individuals (14,22,38) with a significant correlation (r = 0.76) between THR and TV O 2 in one of those studies (22). However, there are also data to support the idea that even if a slower adjustment of HR occurs in older participants, compensatory mechanisms might take place to distribute a larger percentage of the cardiac output to the active muscles so that muscle blood flow is not compromised (71).…”
Section: Why Is V O 2 Kinetics Typically Slower In Older Adults?mentioning
confidence: 90%
See 1 more Smart Citation
“…Other authors further averaged the responses into 5 s (e.g. Gravelle et al, 2012) or into 10 s (e.g. Salvadego et al, 2010) time intervals, although none of them provide a justification for these procedures; an alternative method requiring the averaging of more data according to the number of repetitions was used by Murgatroyd et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Essas alterações refletem, em grande parte, o declínio da capacidade oxidativa mitocondrial, gerando maior dependência de metabolismo anaeróbico em pessoas idosas (36) (38) . Alterações na capacidade de integração sensorial também são descritas com o envelhecimento.…”
Section: Fig3unclassified